Exploring adult education and career opportunities for people with disabilities - Hangya, Dóra (Fogyatékosság és Társadalom)
The study examines the current issues concerning equal opportunity access for People with disabilities from the perspective of Hungarian vocational and adult education. Its aim is to raise awareness regarding the domestic legislative environment concerning the Adult educational opportunities for Adults living with disabilities, in relation with the current European Union objectives and policy tasks yet to be implemented. The study presents a brief analysis of the most recent census data in relation with the educational attainment level and employment rate of People with disabilities, as well as an analysis of the objectives of the Vocational Education And Training 4.0 Strategy revised in 2023 concerning Adult students living with disabilities. In relation to the latter, the study focuses on the framework of inclusive Adult education, the roles of Adult educators, the earlier yet still innovative results of the AEMA project, the inclusive self-assessment matrix, as well as the introduction of potential Hungarian good practices.